AMERICAN LITERATURE AT THE TURN OF THE TWENTIETH CENTURY: TRANSITION, INNOVATION, AND CULTURAL IDENTITY - Iroda Egamberdiyeva Abdurahimovna; Najimov Dilshodbek Hasanboy o‘g‘li (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the transformation of American literature at the turn of the twentieth century, a period marked by significant social, cultural, and artistic change. The study examines how literary movements evolved during this transitional era, moving from realism and naturalism toward modernism. Particular attention is given to the ways in which writers responded to industrialization, urbanization, and shifting cultural values. The research highlights the contributions of authors such as Henry James, Theodore Dreiser, and Edith Wharton, whose works reflect both continuity and innovation in literary forms. Their writings reveal the tensions between tradition and change, as well as the emergence of new narrative techniques and thematic concerns. Furthermore, the article argues that this period played a crucial role in shaping American cultural identity. Literature became a medium through which writers explored issues of class, gender, and individual consciousness, contributing to the development of a distinct national voice in the global literary landscape.